Sexual dimorphism of mental foramen position in peruvian subjects: A cone-beam-computed tomography study - Yalil Augusto Rodríguez-Cárdenas; Manuel Casas-Campana; Luis Ernesto Arriola-Guillén; Aron Aliaga-Del Castillo; Gustavo Armando Ruiz-Mora; Maria Eugenia Guerrero (Wolters Kluwer Medknow Publications, 2020)
Background: The position of the mental foramen (MF) is particularly relevant in dentistry. The incorporation of new imaging techniques, such as cone-beam-computed tomography (CBCT), can be used to identify anatomic dimorphic traits. Aims: This study evaluated the sexual dimorphism of MF position by CBCT among a selected population. Methods: Fifty CBCT images from 20 to 40-year-old subjects (25 men and 25 women) were evaluated. The horizontal position was evaluated using the al Jasser-Nwoku classification to identify the position of the MF in the mandible. Two measurements were obtained on coronal sections to evaluate the vertical position of the MF: the distance from the uppermost alveolar ridge to the upper edge of the foramen and the distance from the inferior edge of the foramen to the lower border of the mandible. Statistical Analysis Used: Comparisons between sexes and sides were performed with Student's t-test and Chi-square tests. Results: The most frequent location of the MF was in line and below of the second premolar tooth in both men and women (P > 0.05). Additionally, significant differences were found between sexes for the distance from the inferior edge of the foramen to the lower border of the mandible in each side (P < 0.001 for the right and left sides). Conclusions: Horizontal position of the MF is not a sexually dimorphic feature and it is predominantly in line and below the second premolar tooth. Women present the MF in a more caudal position, closer to the mandibular base when compared to men.